2023
DOI: 10.1097/md.0000000000033329
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography of the diaphragm in acute exacerbation of chronic obstructive pulmonary disease: A prospective observational study

Abstract: Patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) are prone to diaphragmatic dysfunction. However, dynamic assessment of diaphragmatic function is complex and difficult, and whether the assessment of diaphragmatic function can reflect clinical indicators such as lung function in AECOPD patients remains unclear. We studied diaphragm stiffness and diaphragm stiffening rate (DSR) in AECOPD patients with acute exacerbations ≥ 2 times within 1 year and their correlation with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, 2D-SWE has also been applied to monitor cases of COVID-19, although the results for the detection of sequelae after the discharge were not significant [35]. Similarly, publication of elastography in patients with chronic obstructive pulmonary disease (COPD) showed that decreased diaphragmatic elasticity correlated to disease severity on the Global Initiative for Chronic Obstructive Lung Disease scale stratification [36]. Finally, a sign called 'elasto-lung point' when strain elastography is applied to pneumothorax has been described and can help identify and confirm the conventional 'lung point' [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 2D-SWE has also been applied to monitor cases of COVID-19, although the results for the detection of sequelae after the discharge were not significant [35]. Similarly, publication of elastography in patients with chronic obstructive pulmonary disease (COPD) showed that decreased diaphragmatic elasticity correlated to disease severity on the Global Initiative for Chronic Obstructive Lung Disease scale stratification [36]. Finally, a sign called 'elasto-lung point' when strain elastography is applied to pneumothorax has been described and can help identify and confirm the conventional 'lung point' [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been applied to the study of the elastic properties of the lung parenchyma in chronic obstructive pulmonary disease (COPD) [34]. Two recent studies suggest that diaphragm stiffness estimated by ultrasonography is significantly correlated with pulmonary volumes and spirometric parameters, such as the Tiffeneau index, in COPD, predicting the number of acute exacerbations over time and stratifying disease severity [35,36]. In critically ill patients undergoing mechanical ventilation, diaphragm stiffness estimated by shear-wave elastosonography was correlated with transdiaphragmatic pressure, providing useful information for estimating respiratory load and regulating ventilatory settings [37,38].…”
Section: Technique Of Diaphragm Assessment By Ultrasoundmentioning
confidence: 99%